KEWENANGAN DAN KEDUDUKAN PEREMPUAN DALAM PERSPEKTIF GENDER: SUATU ANALISIS TINJAUAN HISTORIS - Hendri Hermawan Adinugraha; Asep Suraya Maulana; Mila Sartika (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The purpose of this study is to describe the authority and position of women in a gender perspective with an analysis based on a historical approach. This type of research was library research by using content analysis techniques in data processing. The results of this study has been shown that in pre-Islamic era in the Arab Jahiliyyah culture, women received unequal treatment with men (not indicating gender equality). But after Islam came, the teachings of Islam raised the dignity of women, which distinguishes women and men by Allah only the value of his piety. In the classical period (the prophet’s period), women have an important role in all aspects of life, such as in the field of transmission of hadith, war, commerce, and so forth. In the mid-period (Islamic dynasties period), women began to have an important role in political life and state.